(untitled) (Revista Brasileira de Plantas Medicinais, 2000)
The bactericidal activities of Achyrocline satureioides (inflorescences) and Piper aduncum (inflorescences and leaves) extracts were tested against 8 strains of Staphylococcus aureus. These were isolated from milk samples taken from cows with subclinical bovine mastitis. The hexanic and chloroformic extracts of Achyrocline satureioides gave minimum bactericidal concentrations ranging from 14 to 2,400 μg/ml and from 56 to 675 μg/ml, respectively. Piper aduncum yielded a non-active hexanic extract, however its chloroformic extract gave minimum bactericidal concentrations from 237 to 3,800 μg/ml. Ethyl acetate, methanolic, and aqueous extracts did not show bactericidal activity within the range of concentrations tested.